Removal of Methyl Tert-Butyl Ether (MTBE) from Contaminated Water by Photocatalytic Process - A Eslami; S Nasseri; B Yadollahi; A Mesdaghinia; F Vaezi; R Nabizadeh (Tehran University of Medical Sciences, 2009)
"nBackground: Methyl tert-butyl ether (MTBE) has been commercially used as an octane enhancer to replace tetraethyl lead in gasoline since 1979. The high mobility, water solubility, and resistance to natural attenuation associated with MTBE may result in contamination of ground and surface waters. In this investigation the degradation of aqueous MTBE at relatively high concentrations was studied by UV-vis/TiO2/O2 photocatalytic process. The effect of important operational parameters such as pH, oxygen flow, catalyst loading, and irradiation time were also studied."nMethods:Concentration of MTBE and intermediates such as tert-butyl formate (TBF) and tert-butyl alcohol (TBA) were measured using a gas chromatograph equipped with flam ionization detector and combined with headspace sampler."nResults: The time required for complete degradation increased from 15 to 150 min, when the initial concentration was increased from 10 to 500 mg/L. The first order rate constant for degradation of MTBE from the hydroxyl radical was estimated to be 0.266 to 0.033 min-1 as the concentration increased from 10 to 500 mg/L. Study on the overall mineralization monitored by total organic carbon (TOC) analysis showed that in the initial concentration of 100 mg/L MTBE, complete mineralization was obtained after 110 min under UV-vis/TiO2/O2 photocatalytic process."nConclusion: The data presented in this paper clearly indicate that UV/TiO2/O2 advanced oxidation process provides an efficient treatment alternative for the remediation of MTBE contaminated water.